Chemical Removal of Carbonate Scale in Pipes from Oil and Gas Production - Fernando B. Mainier; Renata Jogaib Mainier (Chemical and Materials Sciences - Developments and Innovations Vol. 4, 2024)
Scale deposition and corrosion are the two costliest problems in the oil industry. During the inspection and maintenance carried out in onshore wells in oil and gas production, the presence of adherent scales inside the pipes was revealed. The oil, natural gas and formation water produced in these onshore oil wells come from reservoir rocks rich in minerals such as calcite (CaCO3) and/or dolomite (CaCO3.MgCO3). The formation waters of these wells contain sufficient levels of Ca2+, Mg2+ and HCO3- ions to generate carbonate scale, causing restrictions on the flow of oil and gas production. To return to the initial conditions of oil production, it is necessary to remove the internal carbonate scales with hydrochloric acid injection and to prevent internal corrosion of carbon steel pipes, it is essential to add the corrosion inhibitor to the acid solution. The present study evaluates the dissolution of carbonate scale and the corrosion resistance of carbon steel using gravimetric (mass loss) and electrochemical (polarization) tests. Studies were completed with and without the addition of 250, 500 and 1,000 mg/L propargyl alcohol in HCl solutions with concentrations of 10 wt. % and 15% wt. % at temperatures of 25, 40 and 60 °C. Chemical analyses have revealed that carbonate scales are predominantly composed of 83% calcite, 2% dolomite and 2% kaolinite and the rest is made up of iron oxides and hydroxides. The hydrochloric acid solutions with 10 wt. % and 15 wt. % have become an excellent removing agent with a yield of more than 98%. The results of mass loss assays showed that the addition of propargyl alcohol in 10 wt. % and 15 wt. % HCl provided excellent protection to the carbon steel with an efficiency superior of 95%.